2023
DOI: 10.3389/fpsyg.2023.1149576
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based learning in teacher education: Using Maslow’s Hierarchy of needs to conceptualize instructors’ needs

Abstract: IntroductionSimulation-based learning (SBL) has become an effective tool in the education field, and instructors play a significant role in leading it. Although much is known about participants’ needs, SBL instructors’ needs have yet to be addressed. The study’s goal was to explore SBL instructors’ needs while guiding an SBL workshop using the psychological framework of Maslow’s Hierarchy of Needs.MethodsWe employed a qualitative case-study design, consisting of 68 four-hour-long workshops, held at a teacher-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…According to Maslow's Hierarchy of Needs theory, all social beings have the instinct to avoid harm and when individuals have satisfied their basic needs, they will actively pursue a sense of achievement in their work. This is also in line with the behaviour of pre-service teachers to meet individual needs before enhancing the willingness to educate for national identity [86].…”
Section: B Internally Driven Pathsupporting
confidence: 61%
“…According to Maslow's Hierarchy of Needs theory, all social beings have the instinct to avoid harm and when individuals have satisfied their basic needs, they will actively pursue a sense of achievement in their work. This is also in line with the behaviour of pre-service teachers to meet individual needs before enhancing the willingness to educate for national identity [86].…”
Section: B Internally Driven Pathsupporting
confidence: 61%
“…A study exploring simulation instructors’ self-reported needs, revealed that a ‘sense of competence’, i.e. achieving their highest level of professional functioning through self-reflection, was indeed present amongst many [ 52 ]. Since the vast majority of our sample population was made up of doctors and nurses being actively employed in health care facilities, time constraints and/or workload might be a relevant hypothesis to examine further, especially when striving for (regularly) trained faculty [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pedagogically, it is used within training programmes across various professional disciplines, such as health (Chernikova et al, 2020), social work (Craig et al, 2017) and medical education (Heitzmann et al, 2019). It takes form through different guises, whether physical, virtual or a hybrid of both conditions (Frei-Landau & Levin, 2023), and typically involves students taking part in predetermined activities that reflect their professional field (Rayner & Fluck, 2014). For example, in Dalinger et al (2020)'s study, preservice teachers were physically placed in lab-based sessions that involved using software to simulate parent-teacher discussions, where adult avatars played the role of parents.…”
Section: Simulation In Educationmentioning
confidence: 99%